Prognostic Factors Affecting Long-Term Survival after Resection for Noncolorectal, Nonneuroendocrine, and Nonsarcoma Liver Metastases - Fabio Uggeri; Enrico Pinotti; Marta Sandini; Luca Nespoli; Luca Gianotti; Fabrizio Romano (Gastroenterology Research and Practice)
Aim. To evaluate feasibility and long-term outcome after hepatic resection for noncolorectal, nonneuroendocrine, and nonsarcoma (NCNNNS) liver metastases in a single center. Methods. We retrospectively reviewed our experience on patients who underwent surgery for NCNNNS liver metastases from 1995 to 2015. Patient baseline characteristics, tumor features, treatment options, and postoperative outcome were retrieved. Results. We included 47 patients. The overall 5-year survival (OS) rate after hepatectomy was 27.6%, with a median survival of 21 months. Overall survival was significantly longer for patients operated for nongastrointestinal liver metastases when compared with gastrointestinal (41 versus 10 months; p=0.027). OS was significantly worse in patients with synchronous metastases than in those with metachronous disease (10 versus 22 months; p=0.021). The occurrence of major postoperative complication negatively affected long-term prognosis (OS 23.5 versus 9.0 months; p=0.028). Preoperative tumor characteristics (number and size of the lesions), intraoperative features (extension of resection, need for transfusions, and Pringle’s maneuver), and R0 at pathology were not associated with differences in overall survival. Conclusion. Liver resection represents a possible curative option for patients with NCNNNS metastases. The origin of the primary tumor and the timing of metastases presentation may help clinicians to better select which patients could take advantages from surgical intervention.